KONTRUBUSI REMITENSI TERHADAP PENDAPATAN KELUARGA DI DESA KIAWA - Giovanna M. Masengi; Olly Esry H. Laoh; Eyverson Ruauw; Melissa L.G. Tarore (COCOS, 2013)
AbstrakThis studyaims to determinehow muchcontributionremittancestohousehold incomeinthe villagekiawa. primary dataobtained throughinterviews withrespondents by on a list ofquestions (questionnaire), whereas, secondary dataobtained from theformatprofilereportkiawaruralvillages. data analysis methodsusedin this research isdescriptive.the resultsofthis study indicatethat the contribution ofremittancestohousehold incomein the villageisquitelargekiawa. this is dueto the highremittancessent bymigrant workersIndonesia. basedonthe results ofthis research canbe concluded that, remittancescontributeto thefamily incomeinthe villageis quitelargekiawa. therefore it is verynecessaryfor the familieswhohave familymemberswho work aslaborin the use ofremittancesIndonesia. andit is advisable tobe moreinterestedtobecome a labor ofIndonesia, especiallyforthe unemployed.